Ringing ripples : Collection of poems - Panwar, Sameer (Tamil Nadu Nation Press Media, 2022)
Ringing Ripples is a collection of symbolic poems which meticulously describe emotions, objects from nearby surroundings and the beauty of mother nature. The multi-genre themes of the poem aim to create a gamut of intellectual ideas and thoughts which can help the readers to convert their drops of effort to an ocean of wisdom, thus triggering a reaction of altruism. The author has used subtle imagery, symbols as well as hidden messages for the readers to find out.
Keywords: Collection of Poems